ANALISIS HUKUM PENGGABUNGAN PERKARA KORUPSI DAN MONEY LAUNDERING DALAM SISTEM PERADILAN DI INDONESIA - Chandra Purnama; Bismar Nasution; Sunarmi Sunarmi; Mahmud Mulyadi (USU LAW JOURNAL, 2016)
ABSTRACT   In Indonesia has been increasingly widespread practice of corruption and even to all aspects of life, both at central and local levels. Corruption is referred to as a crime against humanity because it has resulted in poverty and misery of the people. Corruption practices often followed by the Money Laundering Practice, money laundering practices today are very often carried out on the money earned from the evil of corruption. Corruption with Money Laundering has a relationship or association which is very fundamental. It can clearly be seen in article 2, paragraph 1 of Law - Law No. 8 of 2010 on the prevention and eradication of money laundering. In the Act itself known with a term called "predicate offenses" (predicate crime). The results showed that the effective way to make the process of proving the corruption as predicate money laundering Crime Crime is by incorporating (concursus) an indictment, because in addition to looking for financial losses caused by the state Anti-Corruption, Public Prosecutor should also be able to prove that assets - assets and property owned by the defendant obtained by using the proceeds of the Corruption, which is done in various ways which are elements of the Crime of money Laundering, it is intended to provide a more deterrent effect to the defendant. Keywords : Corruption, Money Laundering, Concursus